Epidemiology and outcome of pressure injuries in critically ill patients with chronic obstructive pulmonary disease: A propensity score adjusted analysis. (May 2022) - Martin-Loeches, Ignacio; Rose, Louise; Afonso, Elsa; Benbenishty, Julie; Blackwood, Bronagh; Boulanger, Carole; Calvino-Gunther, Silvia; Chaboyer, Wendy; Coyer, Fiona; Llaurado-Serra, Mireia; Lin, Frances; Rubulotta, Francesca; et al.
Abstract: Background: Pressure injuries are a frequent complication in intensive care unit (ICU) patients, especially in those with comorbid conditions such as chronic obstructive pulmonary disease (COPD). Yet no epidemiological data on pressure injuries in critically ill COPD patients are available. Objective: To assess the prevalence of ICU-acquired pressure injuries in critically ill COPD patients and to investigate associations between COPD status, presence of ICU-acquired pressure injury, and mortality. Study design and methods: This is a secondary analysis of prospectively collected data from DecubICUs, a multinational one-day point-prevalence study of pressure injuries in adult ICU patients. We generated a propensity score summarizing risk for COPD and ICU-acquired pressure injury. The propensity score was used as matching criterion (1:1-ratio) to assess the proportion of ICU-acquired pressure injury attributable to COPD. The propensity score was then used in regression modeling assessing the association of COPD with risk of ICU-acquired pressure injury, and examining variables associated with mortality (Cox proportional-hazard regression). Results: Of the 13, 254 patients recruited to DecubICUs, 1663 (12.5%) had documented COPD. ICU-acquired pressure injury prevalence was higher in COPD patients: 22.1% (95% confidence interval [CI] 20.2 to 24.2) vs. 15.3% (95% CI 14.7 to 16.0). COPD was independently associated with developing ICU-acquired pressure injury (odds ratio 1.40, 95% CI 1.23 to 1.61); the proportion attributable to COPD was 6.4% (95% CI 5.2 to 7.6). Compared with non-COPD patients without pressure injury, mortality was no different among patients without COPD but with pressure injury (hazard ratio [HR] 1.07, 95% CI 0.97 to 1.17) or COPD patients without pressure injury (HR 1.13, 95% CI 1.00 to 1.27). Mortality was higher among COPD patients with pressure injury (HR 1.35, 95% CI 1.15 to 1.58). Conclusion and implications: Critically ill COPD patients have a statistically significant higher risk of pressure injury. Moreover, those that develop pressure injury are at higher risk of mortality. As such, pressure injury may serve as a surrogate for poor prognostic status to help clinicians identify patients at high risk of death. Also, delivery of interventions to prevent pressure injury are paramount in critically ill COPD patients. Further studies should determine if early intervention in critically ill COPD patients can modify development of pressure injury and improve prognosis.